O Colégio Universitário (COLUNI) da Universidade Federal de Viçosa (1965-1981) : formar para a universidade e garantir a qualidade - Hollerbach, Joana D’arc Germano (2016)
This thesis is a result of a study with the objective to analyze the founding and consolidation process of the University College of the Federal University of Viçosa (COLUNI), in the period between 1965 and 1981. The time frame refers to the period from its founding year until the last year that it offered just the third year of high school. We looked to understand how COLUNI integrated itself into the Brazilian education context in the 1960's and 1970's and its relationship with the structural duality of high school in Brazil. We built on the hypothesis that COLUNI, under the argument of preserving the excellence of the university in comparison to the low quality of regular public education, characterized itself as a point of resistance as much as with the school model and pedagogical vigor of the time as with the reforms implanted by the military regime in the national education system by Law 5692/71, that proposed a professional formation at the middle level of education. The methodological option of historical study, starting with the approach by the dialectic method, is justified by looking to investigate the tension relationships between society and the school institution studied here. The search for understanding of the present contradictions in the relations of production led us to believe that the chosen method would be adequate for the analysis in order to understand the history of COLUNI. The methodological procedures are based on historical study. Therefore, the fieldwork consists of data collection from documents - reports, correspondence, class plans, course syllabi - and interviews. Twenty-nine interviews were conducted with former students, former tutors as well as former employees (both teaching staff and secretaries). We arrived to the thesis that the consolidation process of COLUNI was possible in reason by an alignment of the UFV objectives - to form youth prepared to enter the undergraduate course - and the expectations of the military government of technical course training directed toward the Brazilian economy.